PETROLEUM PROVINCES OF THE PARATETHYAN REGION. (15th June 2018) - Boote, D.R.D.; Sachsenhofer, R.F.; Tari, G.; Arbouille, D.
Abstract : Initial crustal collision between Africa and Eurasia in the middle Eocene – early Oligocene enclosed a semi‐restricted Paratethyan seaway of linked basins and platforms across a region stretching from the Eastern Alps to the South Caspian Sea. As the African Plate continued to advance north during the later Neogene, the seaway shrank into a series of more isolated basins separated by the rising Alpine – Carpathian – Caucasus fold‐thrust belts. Organic‐rich oil‐prone Paratethyan source rocks of middle Eocene (Kuma Formation and equivalents) and Oligocene – early Miocene (Maikop and Menilite Beds) ages, and more gas‐prone post‐orogenic mid‐upper Miocene shales, subsequently charged over 2500 accumulations across the region with combined recoverable reserves of 95 billion brl oil‐equivalent (B boe). These accumulations are clustered in discrete petroleum provinces, each with a distinct tectono‐stratigraphic architecture and comprised of one or more petroleum systems. The provinces can be grouped into five broad categories:   Average Reserves Average Field Sizes Fold‐thrust Provinces 60, 980 MMboe 2–590 MMboe Sub‐thrust Provinces 255 MMboe 3.4 MMboe Foreland Provinces 18, 671 MMboe 2–77 MMboe Intermontane Provinces 13, 122 MMboe 1–40 MMboe Black Sea back‐arc Province > 1391 MMboe >33 MMboe The productivity of each province (estimated very approximately from the number of barrels oil equivalent / square kilometre) is extremely variable, and its relationship with the geological factors controlling hydrocarbon entrapment and retention is complex. The most critical of these factors appears to be the quality and distribution of source rocks and post‐charge structural modification.